1999
DOI: 10.1182/blood.v94.6.1961
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Growth Factor-β1 (TGF-β1) Induces Thrombopoietin From Bone Marrow Stromal Cells, Which Stimulates the Expression of TGF-β Receptor on Megakaryocytes and, in Turn, Renders Them Susceptible to Suppression by TGF-β Itself With High Specificity

Abstract: The present study was designed to test the concept that platelets release a humoral factor that plays a regulatory role in megakaryopoiesis. The results showed that, among various hematoregulatory cytokines examined, transforming growth factor-β1 (TGF-β1) was by far the most potent enhancer of mRNA expression of bone marrow stromal thrombopoietin (TPO), a commitment of lineage specificity. The TPO, in turn, induced TGF-β receptors I and II on megakaryoblasts at the midmegakaryopoietic stage; at this stage, TGF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 71 publications
(43 citation statements)
references
References 38 publications
1
40
0
2
Order By: Relevance
“…Large Mk colonies arise from more primitive Mk progenitors. These results are in agreement with previously published data showing that TPO-mediated TGF-b activity is focused on mid CFU-Mk (Sakamaki et al, 1999).…”
Section: Patients D +7 D +14supporting
confidence: 94%
“…Large Mk colonies arise from more primitive Mk progenitors. These results are in agreement with previously published data showing that TPO-mediated TGF-b activity is focused on mid CFU-Mk (Sakamaki et al, 1999).…”
Section: Patients D +7 D +14supporting
confidence: 94%
“…60 45,64 These mediators control HSC proliferation, as noted above, and also constrain MK maturation. [64][65][66][67] PF4 and TGF-could potentially affect other immune cells through their receptors CXCR3B and TGF-R. 68,69 For example, PF4 and TGF-are potent neutrophil activators and promote neutrophil survival and migration, suggesting that MKs could modulate neutrophils before they are released into blood. [70][71][72][73][74][75] TGFis required for Th17 and inducible Treg differentiation.…”
Section: Megakaryocyte Immunoreceptors and Effector Moleculesmentioning
confidence: 99%
“…The concentrations of active TGF-␤ in bone marrow and peripheral blood were measured using the ELISA kit QuantikineTM (R&D Systems, Minneapolis, MN) [5]. Before the assay was run, 1 ml of bone marrow samples was diluted with normal saline (3-fold) containing 100 units/ml of heparin.…”
Section: Assay For Tgf-␤mentioning
confidence: 99%
“…However, its causative mechanism has not been clarified. We have recently reported that thrombopoietin (TPO) from bone marrow (BM) stromal cells plays an essential role in megakaryopoiesis under various pathophysiological conditions [4] and have furthermore identified transforming growth factor (TGF)-␤ as a strong suppressor of megakaryopoiesis [5]. Taking these facts into account, we focused on the effects of TPO and TGF-␤ in patients with cGVHD.…”
Section: Introductionmentioning
confidence: 99%